Prime Ideals in Matrices over Γ-Semihyperrings - Andi Muhammad Anwar; Andi Muhammad Amil Siddik; Ainun Mawaddah Abdal (Department of Mathematics, Hasanuddin University, 2020)
The semihyperring structure is a common form of the hyperring structure with weakening properties. The more general structure is Γ-semihyperring, whose concept is generalized from Γ-semiring. This paper will show that the top matrix Γ-semihyperring is also Γ-semihyperring. The linkage between prime ideal of Γ-semihyperring with prime ideal of a matrix on Γ-semihyperring will also be discussed in this paper.